Gamification of Work Tasks: Effects of Mixed and Individual Game Design Elements on Motivation and Performance - Borgsen,Marcel (2023)
Gamification uses elements of game-designing on mundane tasks to enhance motivation and performance. This study aimed to investigate the effects of gamification on performance, intrinsic motivation and amotivation while doing work tasks. Using a randomized experimental design with the game design elements reward badges and character choice, gamification of in-tray exercises commonly used in Assessment Centres as work tasks were explored. In addition, each game design element was investigated. The results showed that character choice and reward badges had a negative effect on intrinsic motivation (F (1, 93) = 12.600, p = <.001) while being positive on amotivation (F (1, 93) = 11.862, p = <.001). Despite the lower levels of intrinsic motivation, gamification still had a positive effect on performance (F (1, 93) = 10.717, p < .001) due to lower amotivation. The results showed that Gamification has the potential to enhance performance in Assessment Centres and therefore the validity of used methods like in-tray exercises. In future studies, the effects on motivation and performance of individual and mixed game design elements with intrinsic and extrinsic motivational aspects should be researched.
Keywords: Gamification; Game Design Elements; Motivation; Self-Determination; Performance